Factor affecting Malaysia's trade performance / Zuraida Zulkapli - Zulkapli, Zuraida (Faculty of Business and Management, 2006)
The objective of this study is to identify factor affecting Malaysia's trade performance. The evidence of this relationship will focus on trade balance, foreign reserve, foreign direct investment and foreign exchange factors. All of these based on data gathered from 1995 until 2005. The method used in analyze of data is multiple regression analysis. The result from the regression will determine regression equation, R2 ,standard error and hypotheses testing. It will analyze relationship between independent and dependent variables. Therefore, based on findings there are relationship between variables. It means that trade balance, foreign direct investment, foreign reserve and foreign exchange affect the Malaysia's trade performance Trade balance is when totals export minus total import. The different values between them become trade balance. There is trade surplus when total exports exceed the total import and it's become trade deficit when total imports exceed the total export. Foreign direct investment is direct investment in real or physical assets such as factories and facilities in a foreign country. It contributes on total trade. Foreign exchange is the money of a foreign country and always fluctuate depends on foreign exchange market. Malaysia's trade performance over the last decade had been resilient although several global incidents such as the regional currency crisis of 1997/98, the global economic slowdown, the cyclical downturn in the Electric and Electronic sector in 2001, the September 11 incident and the Iraq war and the outbreak of diseases such as SARS and the avian flu.